The effects of public service motivation on criminal justice students’ perceptions of vocational fit - White, D. R. (Criminal justice studies, 2024)
This study investigates the relationships between public service motivation and self-reported perceptions of vocational fit among one cohort of upper-level criminal justice students at a Midwestern university, while controlling for race, gender, age, and political orientation. The data come from a survey administered in the spring of 2021 to criminal justice students in a mandatory class taken between their junior and senior year of their bachelor’s degree program. The findings indicated that increased public service motivations were significantly associated with better perceptions of pre-career vocational fit. Additionally, more conservative political orientations were associated with increased perceptions of fit to criminal justice roles. The study adds to a small but growing body of research applying public service motivation and person-environment fit theory to criminal justice occupations and emphasizes the importance placed on sustaining the value of public service as a possible method of recruiting and maintaining the criminal justice workforce.